PENGARUH EFEKTIVITAS MEDIA SOSIAL INSTAGRAM @BANJARMASINPOST TERHADAP KONSUMSI PEMBERITAAN DI KALANGAN MAHASISWA FISIP UNISKA MAB BANJARBARU - Nullah, M. Amin (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
This study aims to examine the extent to which the effectiveness of Instagram social media @banjarmasinpost influences news consumption among students of FISIP UNISKA MAB Banjarbaru. This research is grounded in the phenomenon of the increasing use of social media by young people, particularly university students, as a primary source of news. The method applied in this study is a quantitative approach with an associative research design. The population consists of active FISIP UNISKA MAB Banjarbaru students from the regular morning classes in semesters 2, 4, 6, and 8 who follow or are familiar with the Instagram account @banjarmasinpost, with a sample of 85 respondents selected through a non-probability sampling technique. The results of the analysis indicate that the effectiveness of Instagram social media @banjarmasinpost has a positive effect on news consumption among FISIP UNISKA MAB Banjarbaru students, with a significance value of 0.001 < 0.05 and a t-value of 10.628 > t-table value of 1.988, which demonstrates a significant influence between the two variables. Furthermore, the effectiveness of Instagram social media @banjarmasinpost contributes 57.6% to the influence on news consumption, while the remaining 42.4% is explained by other variables not included in this study. Keywords: Effectiveness; Instagram Social Media; News Consumption; BanjarmasinPost